(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Since first oil embargo in 1973, the terms "energy crisis" and "energy security" have been constantly in the headlines. Concerns about environmental effects from fossil fuel-based power production have been a source of worry for a long time. Despite efforts to encourage renewable energy sources, fossil fuel-based electricity production continue to control the market. Since coal-fired energy is much more affordable and available to consumers than any other fossil fuel, new nuclear power plants are being built to run at "supercritical" and "ultra supercritical" temperatures and pressures, increasing power generation efficiencies from 30percent to 50percent or more. These new coal technologies promote the use of coal forever for power generation and other purposes, making it more difficult for renewable energy becoming a significant component of the energy mix. To meet growing energy demands and also as part of the National Action Plan for Climate Change, a shift from conventional to non conventional energy sources is required (NAPCC). Solar radiation, on the other hand, is the most abundant as well as direct source of perpetual energy. This article focuses on photovoltaic solar technology for power generation and an assessment of its roof-top use.